2014
DOI: 10.1111/asj.12326
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of zinc protoporphyrin IX‐forming properties of animal by‐products as sources for improving the color of meat products

Abstract: The objective of this study was to obtain fundamental data for improving the color of meat products by using animal by-products. We investigated zinc protoporphyrin IX (ZnPP)-forming properties of various internal organs from pigs and chickens. ZnPP was formed in the liver, heart and kidney, whereas the porcine spleen and bile, which are involved in the metabolism of heme, did not have ZnPP-forming properties. The optimum pH values were different among the internal organs and the ZnPP-forming properties of por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
9
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 17 publications
6
9
0
Order By: Relevance
“…The ability of ferrochelatase to remove and insert the ions is regulated by pH (Chau et al, 2010). The ability of porcine ferrochelatase to form ZnPP is reported to be maximum at a pH of ≤ 6 in in vitro studies (Benedini et al, 2008;Ishikawa et al, 2006;Wakamatsu et al, 2019;Wakamatsu, Murakami, & Nishimura, 2015). It has recently been reported that the optimal pH values for ZnPP formation in porcine skeletal muscles are 5.5 and 4.75 depending on muscle fiber type (Wakamatsu et al, 2019).…”
Section: Effect Of Post Mortem Phsm24hmentioning
confidence: 99%
“…The ability of ferrochelatase to remove and insert the ions is regulated by pH (Chau et al, 2010). The ability of porcine ferrochelatase to form ZnPP is reported to be maximum at a pH of ≤ 6 in in vitro studies (Benedini et al, 2008;Ishikawa et al, 2006;Wakamatsu et al, 2019;Wakamatsu, Murakami, & Nishimura, 2015). It has recently been reported that the optimal pH values for ZnPP formation in porcine skeletal muscles are 5.5 and 4.75 depending on muscle fiber type (Wakamatsu et al, 2019).…”
Section: Effect Of Post Mortem Phsm24hmentioning
confidence: 99%
“…As shown in Table 2, heme is also correlated with pH (r = 0.517; P = 0.010). The Zn-chelatase enzyme has been reported to be affected by pH and takes part in the heme iron demetallation (Chau et al 2011;Wakamatsu et al 2015;Ishikawa et al 2006;Benedini et al 2008). Indeed, Chau et al, (2010) reported that insertion and removal of metal ions by Zn-chelatase is affected by various factors, but the optimal pH for the iron removal from the porphyrin can be set between 5.5-6.0 whereas that for the zinc-ion insertion can be set at pH 7.5-8.0.…”
Section: Relationships Between Physicochemical Parameters and Pigmentmentioning
confidence: 99%
“…Furthermore, pork liver contains a high concentration of Ferrochelatase, which is an enzyme that catalyzes the formation of Zinc protoporphyrin IX (ZnPP). ZnPP is a natural red pigment that, due to its stability to light and heat, might be useful as a means of improving the color of meat products, avoiding or minimizing the controversial use of nitrites/nitrates [8] , [9] , [10] .…”
Section: Introductionmentioning
confidence: 99%